2020
DOI: 10.1101/2020.06.07.137802
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuropilin-1 facilitates SARS-CoV-2 cell entry and provides a possible pathway into the central nervous system

Abstract: The causative agent of the current pandemic and coronavirus disease 2019 (COVID-19)is the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) 1 . Understanding how SARS-CoV-2 enters and spreads within human organs is crucial for developing strategies to prevent viral dissemination. For many viruses, tissue tropism is determined by the availability of virus receptors on the surface of host cells 2 . Both SARS-CoV and SARS-CoV-2 use angiotensin-converting enzyme 2 (ACE2) as a host receptor, yet, their t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
131
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(140 citation statements)
references
References 40 publications
4
131
0
5
Order By: Relevance
“…Neuropilin-1, an integrin-binding protein 23 has recently been reported to be an alternative receptor for SARS-CoV-2 entry 24,25 . NRP1 expression was between one and four orders of magnitude higher than ACE2 expression both in monoculture and on-chip ( Fig.…”
Section: Sars-cov-2 Infection Alters Relative Expression Of Viral Entmentioning
confidence: 99%
“…Neuropilin-1, an integrin-binding protein 23 has recently been reported to be an alternative receptor for SARS-CoV-2 entry 24,25 . NRP1 expression was between one and four orders of magnitude higher than ACE2 expression both in monoculture and on-chip ( Fig.…”
Section: Sars-cov-2 Infection Alters Relative Expression Of Viral Entmentioning
confidence: 99%
“…While a majority of COVID-19 patients present with respiratory symptoms, neurological involvement, including impaired consciousness and headache, have been reported in patients (Mao et al, 2020). To date, human autopsy studies have identified viral RNA transcripts in brain tissues (Puelles et al, 2020;Solomon et al, 2020) and viral proteins in the endothelial cells within the olfactory bulb (Cantuti-Castelvetri et al, 2020) in a handful of people who succumbed to COVID-19. However, the potential of SARS-CoV-2 to infect neurons in the CNS is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 enters the cells using a cell surface receptor, angiotensinconverting enzyme 2 (ACE2) (Hoffmann et al, 2020b(Hoffmann et al, , 2020a. Coentry factors such as TMPRSS2 (Hoffmann et al, 2020a), TMPRSS4 (Zang et al, 2020) and neuropilin1 (Cantuti-Castelvetri et al, 2020;Daly et al, 2020) have also been reported to potentiate infectivity. CoVs are widely believed to enter the cells via two mechanisms: via the endocytic pathway and via a non-endosomal pathway (Ou et al, 2020;Yang and Shen, 2020).…”
Section: Introductionmentioning
confidence: 99%